Маркіян Шашкевич - заспівувач національно-культурного відродження Західної України - Рябчук, М. (Народна творчість та етнографія, 2005)
This article is devoted to the nature of M. Shashkevych understanding of the importance of the formation of its own literature of the Ukrainian nation as a step to the era of renaissance. He understood and supported the transformation from the church language to the live language of the folk and further to the literature language of Ukrainians. Since the creation of its own book language was done under the pressure of other cultures and languages this proñess was very painfull for Ukraine. M. Shashkevych made a lot of practical steps into forcing the development of national language, book writing and book publishing.